4.6k views
5 votes
14x+½(4x+6)=3(x-4)-18

x=____​

User BohdanZPM
by
4.6k points

2 Answers

6 votes

Answer:

x = -
(33)/(13)

Explanation:

Given

14x +
(1)/(2)(4x + 6) = 3(x - 4) - 18 ← distribute parenthesis on both sides

14x + 2x + 3 = 3x - 12 - 18, that is

16x + 3 = 3x - 30 ( subtract 13x from both sides )

13x + 3 = - 30 ( subtract 3 from both sides )

13x = - 33 ( divide both sides by 13 )

x = -
(33)/(13)

User Stive
by
4.6k points
5 votes

Answer:

x=−15/31=−0.484

Explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

14*x+(1)/(2)*(4*x+6)-(3*(x-4)-18*x)=0

STEP 1 Equation at the end of step 1

1

(14x+(—•(4x+6)))-(3•(x-4)-18x) = 0

Simplify

1/ 2

Equation at the end of step 2

1

(14x + (— • (4x + 6))) - (-15x - 12) = 0

2

4.1 Pull out like factors :

4x + 6 = 2 • (2x + 3)

(14x + (2x + 3)) - (-15x - 12) = 0

31x + 15 = 0

Solve : 31x+15 = 0

Subtract 15 from both sides of the equation :

31x = -15

Divide both sides of the equation by 31:

x = -15/31 = -0.484

User Ben Hymers
by
4.8k points